“Mais que uma escola, valores para a vida”: colégio Nossa Senhora Auxiliadora e a educação de mulheres (1957-1958) - Lima, Julyana Jéssyka Gonçalves Casimiro (2022)
This research is part of a series of academic studies on Catholic confessional educational institutions and the formation of women for the teaching profession in the 20th century. We sought to analyze the conditions of possibility for the creation of the Colégio Nossa Senhora Auxiliadora in the city of Sousa - Paraíba, as well as the formation of women for the teaching profession during the years of its implementation and foundation (1957-1958), seeking to understand the relationships among society, school education and religion, and their articulation with the social, cultural and educational models disseminated at that time. The Colégio Nossa Senhora Auxiliadora, locus of the research, was established by Vicar João Cartaxo Rolim, who counted on the collaboration of the Sousense elite and the administration of the Congregation of the Daughters of Saint Teresa of Jesus. The building donated by the Mariz family for educational purposes, located in the city center, was remodeled, furnished and destined for primary, junior high, high school and pedagogical education. In its first year of operation, the school had 218 students enrolled in boarding, day boarding and semi-boarding schools. This study is based on a qualitative approach based on direct and indirect documental analysis as an investigative method, concentrated in the area of History of School Institutions, supported by theoretical and methodological references from Cultural History and Sociology as an analytical axis. In the Brazilian Republic, in face of the modernization and urbanization processes of the Brazilian cities, there was a considerable intensification of social values, of the importance of the family, as well as the role of women, seen as capable of educating and preparing the "new citizen" of the emerging society. In this perspective, with the enlargement of the expansionist project of Catholicism, the Catholic Church and the Sousã elite, in a cooperative regime, saw in a school of nuns the best place to prepare the girls for home and life in the developing society. With the motto "science, faith, citizenship", CNSA encouraged the transformation of society in the light of Christian values, and thus was building an imperishable milestone in local society.